Climate justice in India - Kashwan, Prakash (Cambridge University Press, 2022)
Climate Justice in India brings together a collective of academics, activists, and artists to paint a collage of action-oriented visions for a climate just India. This unique and agenda setting volume informs researchers and readers interested in topics of just transition, energy democracy, intersectionality of access to drinking water, agroecology and women's land rights, national and state climate plans, urban policy, caste justice, and environmental and climate social movements in India. It synthesizes the historical, social, economic, and political roots of climate vulnerability in India and articulates a research and policy agenda for collective democratic deliberations and action. This crossover volume will be of interest to academics, researchers, social activists, policymakers, politicians, and a general reader looking for a comprehensive introduction to the unprecedented challenge of building a praxis of justice in a climate-changed world. This title is also available as Open Access on Cambridge Core.
Title from publisher's bibliographic system (viewed on 03 Nov 2022).
Keywords: Climatic changes -- Government policy -- India.; Climatic changes -- Social aspects -- Inida.; Environmental justice -- India.